Openness to experience as a predictor of L2 WTC. (February 2018) - Piechurska-Kuciel, Ewa
Abstract: This paper aims to provide empirical evidence for the relationship between openness to experience and L2 willingness to communicate (WTC). The study posits that openness as a personality dimension may have a dual effect—both direct and indirect—on one's L2 WTC levels. First, openness directly influences L2 WTC through its stable character, shaping one's cognition, affect and behaviour. Also, it has a possible dual indirect impact by mediating perceived communicative competence and language anxiety. According to the results of step-wise multiple regression, openness can be regarded a significant predictor of L2 WTC, explaining 21% of its variability. It may be concluded that students with high levels of openness demonstrate their stable predispositions to look for gratification through initiating verbal encounters in a foreign language. Together, the variables included in the model explain over 45% of L2 WTC variability, stressing the mediating role of perceived communicative competence (operationalized as self-perceived levels of FL skills) and language anxiety.